Efeito da paisagem na biodiversidade de mamíferos médio e grande porte em um ecótono cerrado – Amazônia - Marchiori, Franciane Aparecida (2019)
Habitat loss and fragmentation of Neotropical forests has increased rapidly in recent decades. It caused severe impacts on the diversity and ecological processes that depend on species associated with the forest. Much research has been developed to understand these effects on the fauna that inhabits the Amazon and Cerrado biomes, while the ecotonal zones of these ecosystems remain poorly studied. The immense heterogeneity of the environments south of the Amazon rainforest brings us unknown how the medium and large mammal groups are using the environments available to them as: Fragments, Corridors and Continuous Forests. We used trap cameras to survey fauna and selected 15 landscapes with variation in forest cover (%). We use this work to describe species richness, number of threatened species and number of records of occurrence of medium and large terrestrial mammals in the Tanguro Long Term Ecological Research (LTER) project at the base of the upper Xingu, Mato Grosso, southern Amazon, Brazil. We recorded 5,633 records from April to September 2018 (118.000 hours of collection) for 24 mammalian species. Forest cover (%) positively influenced the number of threatened species, but it was not important to explain species richness or number of records per landscape. When we analyzed the environments, we observed a clear response of forest species to fragmentation disturbances as an effect of edge quantity, habitat percentage and environmental diversity.